Associations between short-term efficacy and clinical characteristics of infantile hemangioma treated by propranolol. Issue 6 (February 2019) - Wu, Changhua; Guo, Lei; Wang, Liang; Li, Jing; Wang, Changfeng; Song, Dan
Abstract : Abstract: Propranolol is the mainstay of treatment for infantile hemangiomas (IHs) benefited from its low complication in the present study. However, it has an uncertainty treating period with cumbersome methods which may be related to clinical features. This study sought to considered possible influences of short-term efficacy to medication. Retrospective analysis of 82 patients with IHs treated by propranolol was performed. The patients were grouped according to effect (excellent, good and fair/poor). ANOVA or t test was used to assess the relationships between effect and clinical features of IHs. Twenty-seven patients were males and 55 were females. The median age of treatment initiation was 3.5 (±2.11) months. Mean follow-up time for the group was 6.2 months (1.5–16 months). There were no significant associations between short-term efficacy and gender, time points of treatment, diameter of tumor and multifocality. However, tumor thickness was associated with short-term efficacy ( P = .013). Moreover, an obvious difference of short-term efficacy has been found when tumor thickness <1.2 cm. In the present study, tumor thickness was associated with the short-term efficacy in patients with IHs. Propranolol may be gets a better outcome when tumor thickness <1.2 cm at a short time.